Dopant‐Free Hole Transport Materials Based on a Large Conjugated Electron‐Deficient Core for Efficient Perovskite Solar Cells. (21st September 2021) - Hai, Jiefeng; Wu, Hao; Yin, Xinxing; Song, Jiaxing; Hu, Lin; Jin, Yingzhi; Li, Ling; Su, Zhen; Xu, Zhiguang; Wang, Hao; Li, Zaifang
Abstract: Hole transport materials (HTMs) play a significant role in device efficiencies and long‐term stabilities of perovskite solar cells (PSCs). In this work, two simple dopant‐free HTMs are designed with a large conjugated electron‐deficient core. On the one hand, a large coplanar backbone endows enhanced π–π stacking and reduced hole hopping distance. On the other hand, the incorporation of electron‐deficient unit can easily tune the energy levels as well as increase hole mobilities. Combining these two advantages together, 12, 13‐bis(2‐ethylhexyl)‐3, 9‐diundecyl‐12, 13‐dihydro[1, 2, 5]thiadiazole[3, 4‐e]thieno[2″, 3″:4, 5]thieno[2′, 3′:4, 5]pyrrolo[3, 2‐ g ]thieno[2′, 3′:4, 5]thieno[3, 2‐ b ]indole is chosen as the large electron‐deficient core to construct two novel dopant‐free HTMs, Y6‐T and Y‐T. Both Y6‐T and Y‐T behave suitable highest occupied molecular orbital levels, good hole mobilities, as well as strong hydrophobicities. After careful device optimization with a passivation agent, Y‐T delivers an impressive power conversion efficiency of 20.29%, which is higher than that of Y6‐T (18.82%) and doped spiro‐OMeTAD (19.24%). Moreover, PSCs based on Y6‐T and Y‐T show much better long‐term stabilities than spiro‐OMeTAD due to the intrinsic hydrophobicity. Therefore, this work provides a promising candidate as well as a useful design strategy for exploring dopant‐free HTMs, which may pave the way for the commercialization of PSCs. Abstract : Two novel dopant‐free hole transport materials (HTMs) named Y6‐T and Y‐T with a large conjugated electron‐deficient core are developed for efficient perovskite solar cells. The champion power conversion efficiency (PCE) reaches 20.29% for Y‐T‐based device. The Y‐T‐based devices without encapsulation retain over 90% of the initial PCE in air with a relative humidity around 30% after storing for 60 days.